Histopathologic Analysis of Helicobacter pylori Infection in Gastric Biopsies from Patients of Peshawar: An Anatomical and Pathological Perspective - Ali, Momena; Khatoon, Shehla; Nadeem, Saima; ZAMAN, RONAQ (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Helicobacter pylori is a major cause of chronic gastritis and a key risk factor for gastric carcinoma. The burden of infection remains high in developing countries, yet regional data describing its anatomical distribution and histopathological impact are limited. Objective: To determine the frequency, anatomical distribution, and associated histopathological changes of H. pylori infection in gastric biopsies from patients presenting with upper gastrointestinal symptoms in Peshawar. Methodology: A descriptive cross-sectional study was conducted from January 2021 to December 2021. Seventy-two gastric biopsy specimens were collected from the outpatient departments of Hayatabad Medical Complex, Peshawar, and processed at Khyber Medical College. Specimens were evaluated by histopathology using Hematoxylin and Eosin and modified Giemsa staining. Bacterial culture was performed for microbiological confirmation. Results: H. pylori infection was detected in 48 (66.7%) cases by histopathology and 44 (61.1%) by culture. Overall, 48 (66.7%) patients were confirmed to be infected. Overall, 50 (69.4%) patients were confirmed to be infected by combined diagnostic methods. Infection was significantly associated with male gender (p = 0.038) and the 31–40-year age group (p = 0.027). Chronic active gastritis was the most frequent histological finding, while glandular atrophy and intestinal metaplasia were identified in 38% and 26% of positive cases, respectively. The antrum and incisura angularis were the most commonly involved anatomical sites (p = 0.016). Conclusion: H. pylori infection is highly prevalent in Peshawar and is closely associated with chronic and premalignant gastric mucosal changes, emphasizing the importance of early detection and eradication.